Sistem Pakar Pencegahan Stunting untuk Mendukung Pemahaman Ibu Hamil Terhadap Kebutuhan Asupan Gizi Berbasis Android - Hidayatur Rakhmawati; megawati; Nurlaela (Politeknik Negeri Indramayu, 2024)
Stunting is a condition of failure to thrive in toddlers due to lack of nutritional intake for a long time and also due to recurrent infections, the causes of these two factors are influenced by inadequate parenting patterns. Thus, an expert system for stunting prevention is needed that will help provide insight for pregnant women about their nutritional needs and make it easier for parents to consult about stunting prevention and get reminders about nutritional needs during pregnancy. An Android-based stunting prevention expert system to support pregnant women's understanding of nutritional intake needs was built using the forward chaining method and research methods in the form of experimental methods aimed at providing logical information regarding stunting prevention regarding nutritional intake needs. The results of the research show that the forward chaining method is suitable for use, including in the aspect of conclusion results based on questionnaires that have been filled out appropriately and satisfactorily with a percentage of 80%, the information provided is appropriate, resulting in a percentage of 88%, 91% stated that this system helps pregnant women in preventing stunting. , as well as producing conclusions regarding the application, namely the application is easy to use with a percentage of 85%, menu navigation is easy to use with a percentage of 88%, the application display can be seen comfortably with a percentage of 88%.